Hiperalimentação enteral em traumatismos crânio-encefálicos agudos reposição ou dietoterapia? - Schelp, Arthur Oscar [UNESP]; Pellizon, Angela [UNESP]; Burini, Roberto [UNESP] (Academia Brasileira de Neurologia (ABNEURO), 1992)
Os autores apresentam revisão geral sobre a fisiopatogenia do trauma, ressaltando os estados de hipereatabolismo e hipermetabolismo, suas consequências nutricionais, com as particularidades do trauma encefálico. São feitas, também, considerações sobre as vias, composição e volumes das dietas enterais a serem administradas a pacientes com trauma agudo encefálico, assim como são apontadas questões a serem melhor elucidadas.

The authors raise a discussion on nutritional needs of severely traumatized patients under the currently knowledges about the pathophysiology of trauma, particularly in head injury patients. Special attention to the hypermetabolic and hypercatabolic states is given. Some considerations about dietary glucose and protein interactions are made. Finally, the authors expose the diet composition currently used in their institution. Routes and volumes for diet administration are commented. Questions about further studies in some areas of this field are also stated.
Enteral feeding in acute head injury: replacement or therapy?
Keywords: trauma crânio-encefálico; metabolismo; alimentação oral; head injury; metabolism; enteral feeding